2021
DOI: 10.1111/php.13462
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery, Development and Demonstration of Three Caged Compounds

Abstract: An overview of the history, mechanistic aspects and applications is provided for p-hydroxyphenacyl (pHP) and benzoin photoremovable protecting groups, which release biologically important leaving groups upon photolysis with UV light. Also discussed is (7-diethylaminocoumarin-4-yl)methyl (DEACM), a photoremovable protecting group that absorbs visible light. These are followed by the a-keto amides and naphtho-and benzothiophene-2-carboxanilides as caging groups, which eliminate leaving groups via photochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(77 reference statements)
0
7
0
1
Order By: Relevance
“…46,48 In addition to linear hydrocarbons, we explored the photolysis of several cyclic hydrocarbon-containing Cbl conjugates, including the cyclopropyl (8) and cyclobutyl (10) derivatives, in which the ring is directly appended to the Co. Furthermore, we synthesized the corresponding cyclopropylmethyl (8), cyclobutylmethyl (11), and methylcyclohexyl (12) analogs to assess whether the methylene bridge has any influence on photolysis rate of these cyclic species. The photolytic quantum yield for cyclopropyl-Cbl is modest (0.09) relative to other alkyl-Cbl derivatives [e.g., cyclobutyl-Cbl (0.22)].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…46,48 In addition to linear hydrocarbons, we explored the photolysis of several cyclic hydrocarbon-containing Cbl conjugates, including the cyclopropyl (8) and cyclobutyl (10) derivatives, in which the ring is directly appended to the Co. Furthermore, we synthesized the corresponding cyclopropylmethyl (8), cyclobutylmethyl (11), and methylcyclohexyl (12) analogs to assess whether the methylene bridge has any influence on photolysis rate of these cyclic species. The photolytic quantum yield for cyclopropyl-Cbl is modest (0.09) relative to other alkyl-Cbl derivatives [e.g., cyclobutyl-Cbl (0.22)].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 Consequently, we examined the photolysis of several of the alkyl-Cbl conjugates in DMF to assess the impact of a nonaqueous solvent on photolysis rates (Table 2). The conjugates analyzed include aliphatic acyclic (4, 7) and cyclic derivatives (8,12), as well as amino acid (15) analogs. The ethyl-Cbl conjugate behaves similarly in aqueous and organic media, likely due to the relatively simple ethyl ligand having few interactions with the surrounding solvent in either system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without light irradiation, cBMS‐1 did not block PD‐1/PD‐L1 interaction, resulting in suppressed immune activity of Jurkat T cells. With light irradiation at 420 nm, DEACM was removed to release BMS‐1, [ 20 ] which successfully blocked PD‐1/PD‐L1 interaction and triggered the release of cytokines from Jurkat T cells. [ 21–23 ] The study demonstrated the first example of precisely controlling PD‐1/PD‐L1 interaction with light, paving the way to targeted and controlled immune checkpoint blockade for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%